1998
DOI: 10.1002/(sici)1097-0177(199810)213:2<188::aid-aja4>3.3.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Initial retinoid requirement for early avian development coincides with retinoid receptor coexpression in the precardiac fields and induction of normal cardiovascular development

Abstract: Vitamin A requirement for early embryonic development is clearly evident in the gross cardiovascular and central nervous system abnormalities and an early death of the vitamin A-deficient quail embryo. This retinoid knockout model system was used to examine the biological activity of various natural retinoids in early cardiovascular development. We demonstrate that all-trans-, 9-cis-, 4-oxo-, and didehydroretinoic acids, and didehydroretinol and all-trans-retinol induce and maintain normal cardiovascular devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
36
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(37 citation statements)
references
References 38 publications
1
36
0
Order By: Relevance
“…We show that endogenous RA is required to prevent Fgf expression in the posterior lateral mesoderm (including in the posterior region of the SHF). Not only did RA deficiency lead to expanded Fgf8 and Fgf10 (Mlc1v-nlacZ-24-enhancer trap) expression, this expansion occurred at approximately the five-somite stage, when cardiac defects become irreversible in the quail vitamin A-deficiency model (33). Conversely, we saw that excess exogenous RA reduces SHF Fgf8 levels, similar to what has been observed when endogenous RA is increased by blocking the activity of its metabolizing CYP26 enzymes (39).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…We show that endogenous RA is required to prevent Fgf expression in the posterior lateral mesoderm (including in the posterior region of the SHF). Not only did RA deficiency lead to expanded Fgf8 and Fgf10 (Mlc1v-nlacZ-24-enhancer trap) expression, this expansion occurred at approximately the five-somite stage, when cardiac defects become irreversible in the quail vitamin A-deficiency model (33). Conversely, we saw that excess exogenous RA reduces SHF Fgf8 levels, similar to what has been observed when endogenous RA is increased by blocking the activity of its metabolizing CYP26 enzymes (39).…”
Section: Discussionsupporting
confidence: 79%
“…Because restoring Hoxa1 expression in RAdeficient amphioxus embryos can rescue patterning defects (32), we postulate that the lack of Hoxa1 expression in the cardiac field may result in cardiac perturbations found in Raldh2 mutants (4). We found that the earliest events of cardiac RA deficiency were the caudal expansions of SHF gene expression, occurring at a stage when cardiac defects become irreversible in an avian vitamin A-deficiency model (33). We propose that these initial molecular alterations in SHF expression are why RA-deficient heart formation cannot be restored after this time.…”
Section: Discussionmentioning
confidence: 84%
“…RAR␤ mRNA is enhanced by retinoids in mouse (Jiang et al, 1994) and chicken (Lu et al, 1997) embryos. The expression of RAR␣ is downregulated in vitamin A deficient quail embryo and returns to normal levels when RA levels are restored before the 5-somite stage (Kostetskii et al, 1998). Excess RA in this project may turn on or increase certain RA receptor expression or turn off or decrease other receptors, therefore, changing the secretion of the particulate matrix from the myocardium.…”
Section: Discussionmentioning
confidence: 94%
“…These include the injection of large amounts of RA to the yolk, application of RA to the vitelline membrane, and implanting of RA-soaked beads (Eichele et al, 1984;Bouman et al, 1998;Kostetskii et al, 1998). Implanting RA beads was chosen for this study because the beads allows for local delivery of RA to the heart, avoided the toxic effect of large amounts of RA seen in other delivery systems and avoided significant degradation of RA before it reached the intended site of action.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation